Correlation of Blue Light-Induced Phosphorylation to Phototropism in Zea mays L. - Palmer, J. M. (1993)
The physiology of light-induced phototropic curvature has been studied extensively in coleoptiles of grasses, particularly in Avena and Zea mays L. In Z. mays L., we have found that, in addition to curvature, blue light also induces rapid phosphorylation of a 114-kD protein in the tips of coleoptiles, and, in a previous report, we reported several characteristics of the phosphorylated substrate protein and kinase (J.M. Palmer, T.W. Short, S. Gallagher, W.R. Briggs [1993] Plant Physiol 102: 1211-1218). Here, we compare the phosphorylation response to several known aspects of phototropism physiology. Blue light-induced phosphorylation occurs only in the upper portion of the coleoptile and is absent from the node and mesocotyl. The specific activity of phosphorylation is highest in the extreme apical portion of the tip, which is also the site of maximal sensitivity to phototropic stimuli (A. W. Galston [1959] In Physiology of Movements, Encyclopedia of Plant Physiology, Springer, Berlin). Fluence-response determinations indicate that light dosage levels that stimulate curvature also stimulate phosphorylation. However, the threshold for inducing detectable phosphorylation in maize cannot be matched to the threshold for curvature induction. The recovery of sensitivity to phototropic stimuli after exposure to high fluences of light occurs with kinetics that are very similar to those for recovery of the phosphorylation response after a previous high-fluence light exposure. In addition, wavelengths of light in the blue and near-ultraviolet regions of the spectrum that maximally stimulate phototropic curvature also maximally stimulate in vitro phosphorylation in maize. The pattern of stimulation matches the absorption spectra of flavoproteins, which have been proposed as candidates for blue light photoreceptors.